A Novel Design Chewing Gum of Calcium Ions Isolated from Natural Source - Muruganantham, Venkatrajan; Venkateswarlu, Bendi Sri; Chetty, Murali Anjappa (Asian Journal of Biological and Life Sciences)
A pharmaceutical excipient includes calcium carbonate. It is widely used as a diluent in solid dosage forms. As a base for pharmaceutical and dental treatments, as a buffering and dissolution aid for dispersible tablets, as a food additive, and as a calcium supplement, this is utilised. Mineral salts, chiefly calcium carbonate, make up a significant percentage of the eggshell, accounting for around 95 percent of the shell. This Layer farm produces such a large amount of egg shells that their disposal is a problem for the environment. Oral drug delivery system researchers have created new formulations and technologies. The studies show the importance of the oral route among patients. There is an abundance of eggshells that are discarded by the food industry. Transformation of this waste into a pharmaceutical excipient. The conversion of this waste into pharmaceutical excipients will result in cost savings as well as a new supply of raw materials for chewing gum production. The goal of this research is to create eggshell powder as a calcium ion excipient in the production of chewing gum. To obtain a contamination-free material, the egg shells were first ground in a blender and then sterilized in a 20-litre horizontal digital stermax autoclave for 45 min at 122°C. The egg shells were then ground into a fine powder in a Marconi MA 500 ball mill at 249 RPM for 12 hr. The ground eggshell powders were sieved in a No. 80 sieve (aperture of 0.177 mm) to limit particle size. Optical microscopy was used to examine the external morphology of powdered egg shells. Excipients improved the stability of the chewing gum while also enhancing medication release. The quicker the administration of the prescribed chewing gum begins, the better. Scanning electron microscopy was used to examine chicken eggshells with all excipients and pure eggshells (SEM). X-Ray Diffraction was used to examine the chicken eggshell with all excipients and pure eggshell (XRD). Pharmacopea specifications were used to evaluate all formulations. The pH, moisture content, viscosity, weight uniformity, And thickness tests were all within acceptable ranges.
Keywords: Calcium ions; Chicken eggshell calcium carbonate; Chicken eggshell Chewing gum; Chicken eggshell powder; Natural source